Evaluation of coagulation parameters and liver enzymes among alcohol drinkers in Port Harcourt, Nigeria - Adias, Teddy Charles (Dove Medical Press, 2013)
Alcohol is a major contributor to the global burden of disease, disability, and death in high, middle, and low-income countries. Harmful use of alcohol is one of the main factors contributing to premature deaths and avoidable disease burden worldwide and has a major impact on public health. The aim of this present cross-sectional study was to investigate the effect of alcohol consumption on coagulation parameters and liver enzymes of subjects in Port Harcourt, Nigeria. Two hundred adults consisting of 120 alcohol dependent subjects and 80 age, gender-matched nondrinkers aged 25–65 years (mean age 45.25 ± 11.50 years) were enrolled in this study. Of the 120 chronic alcohol drinkers, 37 were dependent on local dry gin, while 83 were dependent on other alcoholic beverages. The mean values of the liver enzymes, aspartate aminotransferase and gamma glutamyl transferase, were significantly higher (P = 0.002 and P = 0.02 respectively) among the chronic alcohol consumers compared with their nondrinker counterparts. Although the value of alanine aminotransferase was higher in the chronic drinkers, it did not reveal any significant difference (P = 0.11). The coagulation parameters, prothrombin time and activated partial thromboplastin time were investigated among chronic drinkers and nondrinkers. The mean value of prothrombin time and activated partial thromboplastin time was significantly higher in the chronic alcohol drinkers compared to the nondrinkers (P = 0.04 and P = 0.02 respectively). We observed a positive and significant correlation between values of liver enzymes, serum gamma glutamyl transferase and aspartate aminotransferase, and values of prothrombin time among alcohol consumers (r = 0.72 and r = 0.68 respectively). The implementation of policies to target harm reduction strategies among alcoholics is urgently needed, alongside the building of a strong base of public awareness and community support required for the continuity and sustainability of alcohol policies. There is also the need for the Nigerian government to enforce tighter regulations and restrictions on the production and distribution of alcoholic beverages to reduce harmful use, and protect young people and other vulnerable groups.